2009
DOI: 10.1007/s00127-009-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

Violence and depressive symptoms during pregnancy: a primary care study in Brazil

Abstract: Pregnant women attending primary care are exposed to high rates of domestic violence, and many have clinically relevant depressive symptoms. Appropriate interventions to avoid or minimize the effects of violence and mental disorders to the well-being of the mothers and their babies are urgently required. Primary care services play an important role in identifying and supporting women at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
13
0
7
Order By: Relevance
“…The ECCAGE (Study of Food Intake and Eating Behavior during Pregnancy) is a cohort study 28,29,30,31,32 of 780 pregnant women based on data collected between June 2006 and February 2007. A total of 59 women (7.5%) refused to participate and nine (1.1%) interrupted the interview before completion, resulting in a final sample of 712 women (91.3%).…”
Section: Methodsmentioning
confidence: 99%
“…The ECCAGE (Study of Food Intake and Eating Behavior during Pregnancy) is a cohort study 28,29,30,31,32 of 780 pregnant women based on data collected between June 2006 and February 2007. A total of 59 women (7.5%) refused to participate and nine (1.1%) interrupted the interview before completion, resulting in a final sample of 712 women (91.3%).…”
Section: Methodsmentioning
confidence: 99%
“…According to Lovisi et al, poverty and violence are risk factors that are often experienced by pregnant women in Brazil and in other developing countries. In addition to pregnancy‐specific vulnerability, women are also exposed to marked social inequality in these countries 910. …”
Section: Introductionmentioning
confidence: 99%
“…That distinction could explain the difference between our findings and the findings reported by those authors, in terms of the prevalence of depression, given that, among population-based studies, the use of a larger number of symptom criteria typically results in a lower prevalence of disease. Manzolli et al (2010) evaluated a population of pregnant females who were treated at primary care clinics, which tends to result in overestimation of the prevalence of mental disorders. In the present study, we evaluated the entire age bracket of adolescence, as defined by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…In the city of Salvador, which is in the north-eastern state of Bahia, Santana et al (2007) evaluated 923 youths between 10 and 21 years of age and found the prevalence of major depression to be 10.4%, higher than the 7.5% reported by Zinn- Souza et al (2008) in a study evaluating 724 students aged 14-18 years in the city of São Paulo, located in the eponymous south-eastern state. In the cities of Porto Alegre and Bento Gonçalves (both in Rio Grande do Sul), Manzolli et al, (2010) evaluated 627 pregnant females treated at primary care clinics, subject ages ranging from 13 to 42 years. The authors found that the prevalence of major depression among the subjects aged r19 years was 25.4%.…”
Section: Discussionmentioning
confidence: 99%